AN ANALYSIS OF FACTORS OF THE AGRARIAN SECTOR DEVELOPMENT IN THE CONTEXT OF NATIONAL FOOD SECURITY - G. Pruntseva (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In the article we analyzed the main problems of the agrarian sector of the economy and the main factors of influence. We presented the classification features factors influencing the food security of the country. We developed the main directions of the development of the agrarian sector in the context of national food security.